Ultra‐Fast and In‐Depth Reconstruction of Transition Metal Fluorides in Electrocatalytic Hydrogen Evolution Processes. Issue 3 (12th November 2021) - Ji, Pengxia; Yu, Ruohan; Wang, Pengyan; Pan, Xuelei; Jin, Huihui; Zheng, Deyong; Chen, Ding; Zhu, Jiawei; Pu, Zonghua; Wu, Jinsong; Mu, Shichun
Abstract: Hitherto, there are almost no reports on the complete reconstruction in hydrogen evolution reaction (HER). Herein, the authors develop a new type of reconfigurable fluoride (such as CoF2 ) pre‐catalysts, with ultra‐fast and in‐depth self‐reconstruction, substantially promoting HER activity. By experiments and density functional theory (DFT) calculations, the unique surface structure of fluorides, alkaline electrolyte and bias voltage are identified as key factors for complete reconstruction during HER. The enrichment of F atoms on surface of fluorides provides the feasibility of spontaneous and continuous reconstruction. The alkaline electrolyte triggers rapid F − leaching and supplies an immediate complement of OH − to form amorphous α ‐Co(OH)2 which rapidly transforms into β ‐Co(OH)2 . The bias voltage promotes amorphous crystallization and accelerates the reconstruction process. These endow the generation of mono‐component and crystalline β ‐Co(OH)2 with a loose and defective structure, leading to an ultra‐low overpotential of 54 mV at 10 mA cm −2 and super long‐term stability exceeding that of Pt/C. Moreover, DFT calculations confirm that F − leaching optimizes hydrogen and water adsorption energies, boosting HER kinetics. Impressively, the self‐reconstruction is also applicable to other non‐noble transition metal fluorides. The work builds the fundamental comprehension of complete self‐reconstruction during HER and provides a new perspective to conceive advanced catalysts. Abstract : A new type of ultrafast and completely reconfigurable transition metal fluoride pre‐catalysts, including CoF2, NiF2, and FeF3 (H2 O)0.33, are found during the alkaline hydrogen evolution reaction process. In terms of CoF2 serving as a representative, its reconstruction mechanism is uncovered.